EXISTENTIAL AND NON-FACTIVE PRESUPPOSITIONINCANDYADVERTISEMENTS,A PRAGMATICS STUDY - Nurchaerani, Meiyanti; Intani, Elsa Nur (Eduscience : Jurnal Ilmu Pendidikan, 2019)
AbstractThis research describes about presupposition in candy advertisements. It is a descriptive-qualititve research.Descriptive study in textual analysis is applied in this study to analyze the presupposition of the utterances produced by slogan in candy advertisements.The purpose of The study is to identify the type of presuppositions in candy advertisements and the phenomena that are appeared in the advertisement in presupposition as one part of pragmatics study.The result of the study showed that there are two types of Presupposition appeared from all of the data. The first type is Existential presupposition and the second type is Non- Factive Presupposition. This research also showed that there are four brands for the Existential Presupposition and one brand for the Non-Factive Presupposition. Keywords:Pragmatics, presupposition,existential presupposition AbstrakPenelitian ini menjelaskan tentang pengandaian dalam iklan permen. Ini adalah penelitian kualitatif. Studi deskriptif dalam analisis tekstual diterapkan dalam penelitian ini untuk menganalisis anggapan ucapan yang dihasilkan oleh slogan dalam iklan permen. Tujuan dari penelitian ini adalah untuk mengidentifikasi jenis prasangka dalam iklan permen dan fenomena. yang muncul dalam iklan dalam presuposisi sebagai salah satu bagian dari studi pragmatik. Hasil penelitian menunjukkan bahwa ada dua jenis Presuposisi yang muncul dari semua data. Tipe pertama adalah presuposisi Eksistensial dan tipe kedua adalah Presuposisi Non-Faktor. Penelitian ini juga menunjukkan bahwa ada empat merek untuk Presuposisi Eksistensial dan satu merek untuk Presuposisi Non-Faktor. Kata kunci: Pragmatik, presuposisi, presuposisi eksistensial